Early improvement of cardiac performance after atrial fibrillation direct current cardioversion. (4th February 2022) - Colombo, C; Degiovanni, A; Ghiglieno, C; Maulini, GM; Patti, G
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Atrial fibrillation (AF) is the most common arrhythmia and one of the most prevalent cardiac disease. Restoring sinus rhythm improves long-term systolic and diastolic function, quality of life and relieve symptoms in patients with symptomatic AF. Purpose: The aim of the study was to evaluate the early effects of AF direct current cardioversion on myocardial deformation using speckle-tracking echocardiography. Methods: 51 patients with persistent AF who underwent successful direct current cardioversion were enrolled (age: 70 ± 9 years; men: 72.5%). Patients with ischemic, dilatative, hypertrophic cardiomyopaties, valvular heart disease, previous cardiac interventions were excluded from the study. Left ventricular ejection fraction was 55.2 ± 7.0%. A transthoracic echocardiography was performed one day before the successful cardioversion and 6 hours after, employing 2d standard echocardiography and speckle-tracking technique to evaluate left atrial, left ventricular and free-wall right ventricular longitudinal strain. Results: Restoration of sinus rhythm led to a reduction of the heart rate (83 ± 14 vs 70 ± 13 bpm, p < 0.001). After about six hours from successful AF direct current cardioversion, we highlighted an increase in left ventricular filling pressure estimated with the ratio E/E' (8.19 ± 0.29 vs 9.34 ± 0.41, p = 0.0016). A significant increase in left atrial longitudinal strain (10.47 ± 0.64% vs 19.76 ± 1.01%, p < 0.001, Figure A) and in left ventricular longitudinal strain (-13.10 ± 0.60% vs -15.86 ± 0.51%, p < 0.001, Figure C) were noticed; also the free wall right ventricular longitudinal strain increased (-12.06 ± 1.16% vs -15.86 ± 1.29%, p = 0.047, Figure B). Conclusion: Restoring sinus rhythm improves cardiac performance as evidenced by the increase in either left atrial and bi-ventricular longitudinal strain, suggesting an amelioration even if after early time.